Patterns of consumption of licit and illicit drugs patients entering an emergency room - Amaro Hinojosa, Marily Daniela (2015)
Background. To identify the arrangement of people to change their consumption behavior of licit and illicit drugs that go to an emergency room.Method. A descriptive cross-sectional design study. The population of patients older than 18 who suffered an accident or injury by violence related to drug use and admitted to the emergency room of a public institution of tertiary care in Monterrey, Mexico, was established. 83 people participated and sampling was conducted in the year 2011.Results. The study oblation consisted mainly of men (fi=79, hi=95,2%), mostly whose occupation was that of worker (fi=54, hi=71,1%), admitted to the emergency room for injuries by violence (fi=42, hi=50,6%). Participants are mostly in the contemplation stage, 62,2% (fi=46) and 77,8% (fi=7), to legal and illegal drugs. Conclusion. Essentially the participants are in the contemplation stage for both legal and illegal consumption of drugs, indicating a correction to their behavior.